2017
DOI: 10.1108/ijqrm-09-2014-0139
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Kaizen process and DFSS methodology for new product development

Abstract: Purpose The purpose of this paper is to propose a new framework for early design stage utilizing the benefits of Kaizen events, and Design for Six Sigma (DFSS) methodology. To gain a better understanding of the proposed method, a case study of a diesel engine development was presented where the proposed methodology was followed. Design/methodology/approach This paper proposes a hybrid Kaizen DFSS methodology consisting of four Kaizen milestone events with pre-work preceding these events. The events are in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The Kaizen philosophy is not easy to adopt and apply in other cultures and much less in Latin American environments such as Ecuador and Mexico; although there is vast literature available on its application (Aoki, 2008; Macpherson et al , 2015; Kumar and Kumar, 2014; Yokozawa and Steenhuis, 2013; Suárez-Barraza et al , 2011; Awad and Shanshal, 2017). Therefore, senior management’s commitment to continuous improvement processes is key to the successful implementation and sustainability of the Kaizen philosophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kaizen philosophy is not easy to adopt and apply in other cultures and much less in Latin American environments such as Ecuador and Mexico; although there is vast literature available on its application (Aoki, 2008; Macpherson et al , 2015; Kumar and Kumar, 2014; Yokozawa and Steenhuis, 2013; Suárez-Barraza et al , 2011; Awad and Shanshal, 2017). Therefore, senior management’s commitment to continuous improvement processes is key to the successful implementation and sustainability of the Kaizen philosophy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studying human behavior and organizational structure becomes a vital task for Kaizen sustainability (Lam et al , 2015; Oprime et al , 2011). Therefore, managers must be leaders in the implementation of improvement programs, developing a sense of belonging in the workers, providing training and professional development, as human talent fosters the culture of change and is the key to the successful achievement of continuous improvement (Awad and Shanshal, 2017). In the face of this, the managerial commitment and the development of human talent are presented as a key factor in this study, when training is planned and structured.…”
Section: Discussionmentioning
confidence: 99%
“…This statement is supported by Farris et al (2009) who showed that KE is capable of adaption to the organization culture. It is also seen as one of the lean tools which assist to ensure that operations become more smoothly by removing wasteful activities that are of no value from the customer perspective (Awad and Shanshal, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Awad and Yassir (2017) presented a case study of a diesel engine development, where a framework of a new methodology was proposed by utilizing the benefits of Kaizen events and design for Six Sigma methodology (define, characterize, optimize and verify). The result concluded that a few key enablers should be available such as management buy-in and support, effective resources utilization and proper planning.…”
Section: Literature Reviewmentioning
confidence: 99%